On Substantive Changes to Contracts Under the United Nations Convention on Contracts for the International Sale of Goods - Yuqing Wang (Studies in Law and Justice, 2023)
First of all, it is important to clarify the premise that the most fundamental basis for the sale and purchase of goods between the international community and countries is in fact the contract for the sale and purchase of goods concluded between the buyer and the seller, and that this contract is the basis for the clarification of their rights and obligations between the parties and for the act of performance. The contract shall be formed on the basis of the act of offer and promise between the parties, so that the validity of the offer and promise has a direct influence on the formal formation of the contract and the subsequent act of sale and purchase of goods. National laws differ as to whether a promise must be identical to an offer. For example, in the common law system there is the well-known “mirror image principle”, which requires a high degree of conformity. Article 19 of the United Nations Convention on Contracts for the International Sale of Goods (CISG), however, provides for this in three main clauses. [i]Even though national laws and international treaties such as the CISG contain specific provisions on offers, promises and material changes to contracts, there is still much uncertainty in practice. This essay will extend the discussion of material change in contracts through a specific international trade case and will focus on the CISG provisions on material change in contracts and their content. Chapter 3 will provide reflections on material change based on the first two papers.